-2(x-8)=6(x+4)-8

Simple and best practice solution for -2(x-8)=6(x+4)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-8)=6(x+4)-8 equation:


-2(x-8)=6(x+4)-8

We simplify the equation to the form, which is simple to understand
-2(x-8)=6(x+4)-8

Reorder the terms in parentheses
+(-2x+16)=6*(x+4)-8

Remove unnecessary parentheses
-2x+16=+6+*(+x+4+)-8

Reorder the terms in parentheses
-2x+16=+(+6x+24)-8

Remove unnecessary parentheses
-2x+16=+6x+24-8

We move all terms containing x to the left and all other terms to the right.
-2x-6x=+24-8-16

We simplify left and right side of the equation.
-8x=0

We divide both sides of the equation by -8 to get x.
x=-0

See similar equations:

| 5x+8-7x-12= | | y=2x^2+36x+168 | | 5y+6x-3y-5x+4x= | | 5y+6x-3y-5y+4x= | | 15m-9=21 | | -2(x-8)=(6x+4)-8 | | 3.45x+2.5y=52 | | 2r-5=1r | | -2x(x-8)=(6x+4)-8 | | -6r-10s+8r+4s-6= | | x^2+2x=89 | | 3x^4+9x^3-25x^2+15x-50=0 | | 2(5+-.5y)+y=10 | | 9y-2+9y=6 | | 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 | | 7t-4.6=10.1 | | 3(xy+w*w)+2xy-2w*2w= | | 9w-18+5w+2=180 | | 9.5+p-6.8=7.3 | | -5s+9=-6 | | (5y+5)-5y=5 | | 15g-3(4g-6)=3g+9-9g | | 6+2x=4x-2 | | 2x+1=10x-3(x-1) | | 3y^2-15y=12 | | x^2+x-80=0 | | 6y+7=5y-5 | | 4a+2b-3-6a-5b= | | 5.5y=71.5 | | 7-6a=7a |

Equations solver categories